L’Écran du bestiaire - Jesse Welton (Francosphères)
The most critically successful works of two Central African novelists writing in French, Alain Mabanckou and Patrice Nganang, are told from the point of view of a narrator who, for one reason or another, could be considered intellectually inferior to the average person. This article will show that by appropriating negative colonial stereotypes of Africans as child-like or animal-like, writers are able to provide a counter-discursive response to these stereotypes and gain greater stylistic freedom to indigenize the former colonial language, thanks to the intermediary of what we will call the intellectually subordinate narrator – a narrator who the reader expects, and therefore accepts, to be cognitively different. We will examine how this phenomenon works as a form of strategic exoticism in Mabankou’s Mémoires de porc-épic (2006) and Nganang’s Temps de chien (2001).